Studi Kasus Penatalaksanaan Gizi Pada Pasien Anak Dengan Diagnosa Hiperleukositosis, ec Susp Leukemia dd limfoma Di Ruang PHCU(Violet) RSUP Prof. Dr. I.G.N.G Ngoerah Denpasar - Supiyadnya, I Gusti Ngurah; Rinayanti, Ni Made; Sahariah Rowa, Sitti; Raul, Suriani (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2025)
Cancer is a disease that requires special attention. Leukemia is the most common malignant cancer found in children. Nutritional care plays an important role in the dietary management of pediatric cancer. Proper dietary regulation is expected to help prevent weight loss caused by the pathological condition. In addition, dietary management can also help maintain laboratory values in pediatric cancer patients.The purpose of this case study is to provide nutritional care for a patient with Hyperleukocytosis + Bicytopenia suspected malignancy + observation of lymphadenopathy suspected Leukemia versus lymphoma through appropriate nutritional intervention to prevent further complications, improve metabolic conditions, and enhance the quality of life of the patient treated at PHCU Violet, Prof. Dr. I.G.N.G Ngoerah General Hospital. This research is a case study using the Nutritional Care Process (NCP) approach, which includes: nutrition screening (STRONGkids), assessment (anthropometric, biochemical, clinical, and dietary data), nutrition diagnosis, nutrition intervention (diet and education), and monitoring and evaluation. The study was conducted at Prof. Dr. I.G.N.G Ngoerah General Hospital in July 2025 with a six-day intervention period. Initial observations before the intervention showed that the patient was at high risk of malnutrition, underweight, and laboratory values had not reached the normal range. The nutritional intervention provided was a high-protein high-calorie (HPHC) soft-texture diet totaling 3,180 kcal, gradually administered starting from 50% of the patient's needs. Observations showed an increase in nutrient intake levels and improvement in physical clinical condition, although there was no weight gain and laboratory values had not reached normal limits. After receiving education, the patient and the patient's family were willing to follow the recommended diet.